Natural Language Generation Systems
XI, 389 p.
Keywords: Natural language generation is a field within artificial intelligence which looks ahead to the future when machines will communicate complex thoughts to their human users in a natural way. Generation systems supply the sophisticated knowledge about natural languages that must come into play when one needs to use wordings that will overpower techniques based only on symbolic string manipulation techniques. Topics covered in this volume include discourse theory, mechanical translation, deliberate writing, and revision. Natural Language Generation Systems contains contributions by leading researchers in the field. Chapters contain details of grammatical treatments and processing seldom reported on outside of full length monographs.